2017
DOI: 10.14639/0392-100x-1417
|View full text |Cite
|
Sign up to set email alerts
|

Non-surgical management of chronic rhinosinusitis with nasal polyps based on clinical-cytological grading: a precision medicine-based approach

Abstract: La rinosinusite cronica con polipi nasali (CRSwNP) è una malattia cronica nasosinusale, a eziologia infiammatoria, con significativo impatto negativo sulla qualità di vita dei pazienti. La CRSwNP rappresenta ancora oggi una sfida terapeutica per lo specialista ORL, sia per la comprensione della sua eziopatogenesi, sia per il suo controllo clinico ed è questo è testimoniato dalla alta incidenza di recidiva dopo trattamento. Abbiamo voluto verificare l’ipotesi che un approccio terapeutico nuovo, standardizzato, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 36 publications
0
27
0
Order By: Relevance
“…Actually, authors discuss on the best procedure to define local inflammation and the most common used techniques include: nasal biopsy, nasal brushing or scraping (nasal cytology), nasal lavage fluid and nasal suctioning of secretions [22][23][24][25][26] . Authors [27][28][29] have suggested that diagnosis of eosinophilic CRS requires quantification of the numbers of eosinophils, i.e. number/high powered field (hpf), which may vary in the literature (8-12/hpf) and which should be achieved by analysing at least three of the most dense collections of eosinophils (very rich fields) in the samples counted at hpf (~400x).…”
Section: Management Based On Phenotyping and Endotyping Of The Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Actually, authors discuss on the best procedure to define local inflammation and the most common used techniques include: nasal biopsy, nasal brushing or scraping (nasal cytology), nasal lavage fluid and nasal suctioning of secretions [22][23][24][25][26] . Authors [27][28][29] have suggested that diagnosis of eosinophilic CRS requires quantification of the numbers of eosinophils, i.e. number/high powered field (hpf), which may vary in the literature (8-12/hpf) and which should be achieved by analysing at least three of the most dense collections of eosinophils (very rich fields) in the samples counted at hpf (~400x).…”
Section: Management Based On Phenotyping and Endotyping Of The Diseasementioning
confidence: 99%
“…), IgE either in blood or tissue, anti-staphylococcal IgE, periostin and other future potential biomarkers] are at the moment the best way to predict the likely natural course of disease and prognosis in terms of disease control after surgery. Based on this concept, many authors 21,28,[30][31][32][33][34] have tried to identify the best way to predict the natural history of the disease, facilitating counseling the patient on the expected outcome of the surgery and helping to establish the best postoperative medical management that can offer the best chance to control patient's symptoms. Finally, identification of endotypes is essential for individualisation of therapy.…”
Section: Management Based On Phenotyping and Endotyping Of The Diseasementioning
confidence: 99%
“…In the present small pilot study, almost all asthmatic patients (five of six) showed the presence of eosinophilia in both nasal and bronchial specimens and patients with nasal and bronchial eosinophilia seem to benefit less, in terms of FEV 1 , from surgery. This may confirm a further role for both nasal and bronchial cytology in predicting the outcomes of ESS, at least at the level of the lower airways 25 and may define a group which could benefit from treatment with novel monoclonal antibodies targeting Type 2 inflammation 26 . Also, based upon this evidence, it can be suggested that, even in absence of specific lower airway disorders, all patients with CRS should undergo a pulmonary medical examination and cytology in order to predict and better define the results of surgery.…”
Section: Discussionmentioning
confidence: 59%
“…Values ≥ 50 identify a severe score 17 . Clinical-Cytological Grading has been previously described in detail elsewhere 11,12 . Briefly, CCG is a score based on both nasal cytology findings and comorbidities, including asthma, allergy and ASA hypersensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, neither prognostic measure assesses inflammatory pattern or comorbidity. In this regard, a clinical-cytological grading (CCG) has been proposed to assess patients with CRSwNP 11 . This tool allows obtaining useful clinical information that can also be collected over time 12 .…”
Section: Introductionmentioning
confidence: 99%